Influence of the diversity of bacterial isolates from drinking water on resistance of biofilms to disinfection - Simões, Lúcia C. (2010)
Single- and multispecies biofilms formed by six drinking water-isolated bacterial species were used to assess their susceptibilities to sodium hypochlorite (SHC). In general, multispecies biofilms were more resistant to inactivation and removal than single biofilms. Total biofilm inactivation was achieved only for Acinetobacter calcoaceticus single-species biofilms and for those multispecies biofilms without A. calcoaceticus. Biofilms with all bacteria had the highest resistance to SHC, while those without A. calcoaceticus were the most susceptible. A. calcoaceticus formed single biofilms susceptible to SHC; however, its presence in multispecies biofilms increased their resistance to disinfection.